Knowledge management application in higher education institutions Through the Six Sigma methodology - Benbertal, Abdelkader (Dirassat Journal Economic Issue, 2016)
We tried through this study model steps according to the methodology of Six Sigma can be administrators and leaders in institutions of higher education followed for the application of knowledge management in their institutions, starting with the identification and definition of the problem that stands in front of them when the application of this concept, with the identification of all the variables that can affect that such as information technology and the organizational culture and knowledge of all the concepts of knowledge management...etc. and then measuring these variables using statistical models and quantitative and qualitative indicators, then a set of solutions to be applied on the reality and monitoring all results obtained with the correct distractions that exist.